A mindset favoring decentralization encourages individualized service. Issue 8 (11th October 2021) - Enos, Gary A.
Abstract : Frank Blalark, Ph.D., encountered a much more decentralized operation when he made the transition to Registrar at Duke University from holding the same post at Purdue University. While variations among the colleges at Duke can present challenges in scheduling and other operational areas, Blalark sees the structure as ideal for tailoring the student experience to individual circumstances.